A KAP STUDY AND SURVEY OF EATING HABITS AMONG MEDICAL FACULTY AT MEDICAL COLLEGE IN SOUTH INDIA - Prakash (Retd), Colonel Jai (Indian Journal of Community Health, 2015)
Introduction: Nutrition intervention is a component of first step therapy for many common diseases including Cardiovascular Diseases, Diabetes Mellitus and Obesity and its role in health promotion, disease-prevention & treatment of chronic diseases is well recognized. Rationale: Nutrition knowledge plays an important role in public health and also interfaces significantly and relevantly with every field of medicine. However physicians’ knowledge on this issue is not very satisfactory. Objective: The objective of present study was to assess nutritional knowledge, attitude and practices pertaining to eating habits among medical faculty of a medical college of South India and also their feedback on present medical curriculum at MBBS level dealing with dietary issues. Material & Methods : It was a cross-sectional study conducted among almost all faculty members (150) participated in the study voluntarily. Faculty members were asked to complete a self-administered questionnaire about KAP and dietary habits through multiple-choice questions based on balanced diet, containing a variety of food in quantities and proportion, derived from green leafy vegetables, fresh fruits, milk, curd, egg, pulse, rice and cereals. Results: Nutritional knowledge was 70 % (mean score of correct answers), 78% scored 60-80% marks & 20% scored less than 60% and majority (79.4%) of them have healthy eating habits. 40% faculty members were over weight (BMI 23-24.9) and 40% were obese (BMI >25). Most of the members replied that the medical curriculum was inadequate or just adequate in dealing with the dietary issues; 68.6% of them were of the opinion that comprehensive nutrition curriculum is needed; 66% suggested a separate nutrition department. Conclusion: A total 150 members participated in the survey voluntarily. Their nutritional knowledge was found to be 70 % and majority (70.4%) of them have healthy eating habit. Most of the members replied that the medical curriculum is inadequate in dealing with dietary issue and suggested comprehensive nutrition-curriculum.